COVID-19 Mortality and Case-Fatality Rates in Sergipe State, Northeast Brazil, From April to June 2020 - Martins-Filho, Paulo R.; Araújo, Adriano A. S.; Góes, Marco A. O.; de Souza, Mércia S. F.; Quintans-Júnior, Lucindo J.; Martins, Natália; Santos, Victor S. (Frontiers in Public Health, 2021)
Information on how coronavirus disease 2019 (COVID-19) mortality is related to population characteristics in low- and middle-income countries is still limited. We described the deaths from COVID-19 in Sergipe state, Northeast Brazil, from April 2 to June 27, 2020. For this purpose, we conducted a study comprised of (i) a case-series study of all deaths due to COVID-19 and (ii) a population-based study to verify the behaviour of the mortality and case-fatality rates (CFR) related to COVID-19. Data from 605 deaths due to COVID-19 were used to describe the characteristics of individuals with the disease, as well as the differences in gender, age, and comorbidities. Additionally, population data were extracted to estimate the mortality and CFR by population stratum. We also performed an adjusted CFR analysis including a time lag of 14 days between the onset of symptoms and reporting deaths. Of the 605 patients included in this study, 321 (53.1%) were males and the median age was 67.0 years. Most patients (n = 447, 73.9%) who died from COVID-19 had at least one pre-existing clinical condition. The mortality rate was 29.3 deaths per 100,000 inhabitants and the crude CRF was 2.6% (95% CI 2.4–2.8). CFR was higher in males (3.1%, 95% CI 2.8 – 3.4; p-value <0.001) and people aged ≥60 years (14.2%, 95% CI 13.0–15.6; p-value = 0.042). About 25% of patients died during the first 24h post-hospital admission. The adjusted CFR for a 14-day time-lag was approximately 2-fold higher than the crude CFR over the study period.